A Comprehensive Algorithm for Management of Neuropathic Pain. (1st June 2019) - Bates, Daniel; Schultheis, B Carsten; Hanes, Michael C; Jolly, Suneil M; Chakravarthy, Krishnan V; Deer, Timothy R; Levy, Robert M; Hunter, Corey W
Abstract: Background: The objective of this review was to merge current treatment guidelines and best practice recommendations for management of neuropathic pain into a comprehensive algorithm for primary physicians. The algorithm covers assessment, multidisciplinary conservative care, nonopioid pharmacological management, interventional therapies, neurostimulation, low-dose opioid treatment, and targeted drug delivery therapy. Methods: Available literature was identified through a search of the US National Library of Medicine's Medline database, PubMed.gov. References from identified published articles also were reviewed for relevant citations. Results: The algorithm provides a comprehensive treatment pathway from assessment to the provision of first- through sixth-line therapies for primary care physicians. Clear indicators for progression of therapy from firstline to sixth-line are provided. Multidisciplinary conservative care and nonopioid medications (tricyclic antidepressants, serotonin norepinephrine reuptake inhibitors, gabapentanoids, topicals, and transdermal substances) are recommended as firstline therapy; combination therapy (firstline medications) and tramadol and tapentadol are recommended as secondline; serotonin-specific reuptake inhibitors/anticonvulsants/NMDA antagonists and interventional therapies as third-line; neurostimulation as a fourth-line treatment; low-dose opioids (no greater than 90 morphine equivalent units) are fifth-line; and finally, targeted drug delivery is the last-line therapy for patients with refractory pain. Conclusions: The presented treatment algorithm provides clear-cut tools for the assessment and treatment of neuropathic pain based on international guidelines, published data, and best practice recommendations. It defines the benefits and limitations of the current treatments at our disposal. Additionally, it provides an easy-to-follow visual guide of the recommended steps in the algorithm for primary care and family practitioners to utilize.